ISOLATION AND IDENTIFICATION OF Escherichia coli ISOLATED FROM LAYER CHICKEN IN CHICKEN VILLAGE, NORTH LOMBOK - Alfiana Laili Dwi Agustin; Kholik (SANGKAREANG, 2018)
Escherichia coli in poultry can cause colibacillosis,If layer chicken in a poultry village is attacked by colibacillosis it will cause significant losses. Besides colibacillosis has become a concern in foodborne phatogen and stated risk of transmission to human. Based on this fact, we want to isolation and identification whether the cause of diarrehea in layer chickens in Kampung Unggas is E. coli because it’s risk to animal, human and environment health, and for effective medical treatment in layer chicken.The results of the recapitulation show that from 32 samples tested 27 positive (Prevalence positive samples 84%) of E. coli with biochemical test results such as previous studies